Interleukin‐1 Receptor‐1 Deficiency Impairs Metabolic Function in Pregnant and Non‐Pregnant Female Mice. Issue 1 (15th December 2019) - Plows, Jasmine F; Vickers, Mark H; Ganapathy, Thashma P; Bridge‐Comer, Pania E; Stanley, Joanna L; Reynolds, Clare M
Abstract : Scope: Glucose intolerance during pregnancy is associated with short‐ and long‐term maternal and offspring health consequences. In young male mice, knockout of the major pro‐inflammatory mediator interleukin‐1‐receptor‐1 (IL1R1) protects against high‐fat diet (HFD)‐induced glucose intolerance and metabolic dysfunction. This phenotype has not been examined during pregnancy. The hypothesis that IL1R1 depletion will protect females against HFD‐induced glucose intolerance and metabolic dysfunction before, during, and post pregnancy is tested. Methods and results: C57BL/6J control and IL1R1 knockout (IL1R1 −/− ) mice are randomized to either a control diet (10% kcal from fat) or HFD (45% kcal from fat), and three distinct cohorts are established: nulliparous, pregnant, and postpartum females. Contrary to the authors' hypothesis, it is found that IL1R1 −/− does not protect against glucose intolerance in nulliparous or pregnant females, and while control HFD animals see a resolution of glucose tolerance postpartum, IL‐1R1 −/− mice remain impaired. These effects are accompanied by adipocyte hypertrophy, hyperleptinemia, and increased adipose tissue inflammatory gene expression. Maternal genotype differentially affects fetal growth in male and female fetuses, demonstrating sexual dimorphism in this genotype prior to birth. Conclusions: These findings suggest that IL1R1 signaling is important for normal metabolic functioning in females, during and outside of pregnancy. Abstract : Blocking the action of IL‐1R1 signaling does not improve high‐fat dietinduced metabolic function during pregnancy and appears to worsen metabolic health post‐partum. IL‐1R1 −/− inhibits the maturation of fat cells by reducing gene expression of adipogenic markers resulting in adipocyte expansion. This contributes to metabolic dysfunction and glucose intolerance as well as a sex‐specific effect on placental nutrient transport.